2020
DOI: 10.3390/vetsci8010001
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and Tryptophan Serum Concentrations in Shelter Dogs Showing Different Behavioural Responses to a Potentially Stressful Procedure

Abstract: In mammals, serotonin (5-HT) levels depend on the availability of tryptophan (TRP). Low 5-HT concentrations have been linked to behavioural disorders in dogs. This study aimed at investigating possible differences in dogs’ serum TRP and 5-HT concentrations according to their behavioural response to a potentially stressful procedure. Thirty-nine physically healthy shelter dogs, 15 females and 24 males, mean age = 5.6 years, were categorized by a certified veterinary behaviourist according to their behavioural r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 64 publications
(93 reference statements)
1
7
0
Order By: Relevance
“…The average serotonin value in medium breed shelter dogs was 397.62 ng/mL, similar to the results obtained by Alberghina et al [ 24 ], who determined average serotonin values of 400 ng/mL. Riggio et al [ 34 ] observed no association between serum TRP and 5-HT levels in their sample of shelter dogs. Because it is widely accepted that TRP and 5-HT concentrations are correlated in the brain, negative findings may be at least partially explained by the role of the blood–brain barrier, regulating the passage of TRP from peripheral to central circulation and that of 5-HT in the opposite direction.…”
Section: Discussionsupporting
confidence: 86%
“…The average serotonin value in medium breed shelter dogs was 397.62 ng/mL, similar to the results obtained by Alberghina et al [ 24 ], who determined average serotonin values of 400 ng/mL. Riggio et al [ 34 ] observed no association between serum TRP and 5-HT levels in their sample of shelter dogs. Because it is widely accepted that TRP and 5-HT concentrations are correlated in the brain, negative findings may be at least partially explained by the role of the blood–brain barrier, regulating the passage of TRP from peripheral to central circulation and that of 5-HT in the opposite direction.…”
Section: Discussionsupporting
confidence: 86%
“…Although, urinary neurotransmitter deviations have been previously associated with different neuropsychological conditions in humans, those results were not transferable to the investigated canine population, and its value for canine behavioral medicine could not be confirmed from these results. This lack of conformity is following some earlier serum serotonin level studies and may be explained by the fact that a direct correlation between the central nervous system (CNS) and the urinary neurotransmitter levels only have been shown to a limited extent in previous studies (18,19,54,55). During neurotransmitter transfer through the body, transporters of the blood-brain barrier (BBB) and the kidney modulate their concentration, whereby the BBB is not permeable for every neurotransmitter (18).…”
Section: Discussionmentioning
confidence: 80%
“…Oral melatonin administration did not affect cortisol concentration in intact female dogs. Two possible explanations have been suggested to be responsible for the effect of melatonin on reducing cortisol concentration: (a) melatonin increases serotonin concentration, and increased serotonin, in turn, decreases cortisol concentration in animals with aggressive behaviour and during stress conditions (Riggio et al., 2021 ) and (b) it is possible that melatonin reduces cortisol secretion and concentration through its receptors in the adrenal gland (Frank et al., 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin is a neurotransmitter with various regulatory functions in physiologic, emotional and behavioural processes. There is an association between aggressive behaviour and low levels of serum serotonin and 5‐hydroxyindoleacetic acid, the primary metabolite of serotonin in dogs, in the cerebrospinal fluids of dogs (Riggio et al., 2021 ). Serotonin is the key intermediate in melatonin synthesis from tryptophan (Zhao et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%